SABUN MANDI ANTIOKSIDAN DARI BERAS MERAH DAN VIRGIN COCONUT OIL (VCO) - Rita, W.S.; Suirta, I.W.; Santi, S.R.; Sahara, E. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i04.p01, 2023)
Brown rice extract and VCO have antioxidant activity, so they can be used as active ingredients in the making of antioxidant bath soap. The purpose of this service is to provide training in making antioxidant soap by using brown rice extract and VCO as active ingredients. Soap making begins with mixing the oil used, one of which is VCO, then reacting it with an alkaline solution, after thickening, the active ingredient brown rice extract, and other ingredients are added to improve the quality of the soap. Brown rice extract is used as an active ingredient in antioxidants, as well as a natural coloring agent for soap. The training was conducted in the presence of PKK mothers in Banjar Penganggahan, Tengkudak Village, Penebel, Tabanan, Bali. The village has made VCO independently, but they have problems with its utilization and marketing. Therefore, this soap-making training also helps PKK mothers in utilizing the VCO. The activity was carried out on Tuesday 10 August 2021, with 17 participants. The method used is lectures and practice of making soap. The brown rice soap produced complies with the Indonesian National Standard (SNI) and has antioxidant properties with an IC50 value of 264.64 ppm (DPPH method). By carrying out this service, the knowledge of the mothers about the benefits of the ingredients used and how to make soap has increased. It is hoped that this red rice soap product from Banjar will be produced on a home industry scale. Keywords: Antioxidant, DPPH, Oryza nivara. Soap, VCO.